Comparative Analysis of Laparoscopic Peritoneal Lavage and Sigmoidectomy for Treating Perforated Diverticulitis (Medical Forum Monthly, 2023)
Objective: The main objective of the study is to find the comparative analysis of laparoscopic peritoneal lavage and sigmoidectomy for treating perforated diverticulitis.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at the DHQ Hospital in Gujranwala from June 2022 to January 2023.Materials and Methods: The study included a total of 45 patients who were diagnosed with perforated diverticulitis and underwent either laparoscopic peritoneal lavage or sigmoidectomy as the primary surgical intervention.Results: Data were collected from 45 patients according to inclusion and exclusion criteria. 25 patients undergoing laparoscopic peritoneal lavage and 20 patients undergoing sigmoidectomy. The mean age of the study population was 57.6±8.2 years. In terms of surgical procedures, it was associated with a shorter mean operative time compared to sigmoidectomy (p<0.001). Intraoperative complications were rare in both groups, with no significant differences observed. Analysis of postoperative complications revealed that the laparoscopic peritoneal lavage group had a lower overall complication rate compared to the sigmoidectomy group (20% vs. 35%, p=0.250).Conclusion: It is concluded that laparoscopic peritoneal lavage may offer advantages over sigmoidectomy in terms of shorter operative time, lower overall complication rates, shorter hospital stay, and potentially quicker return of bowel function.